2006
DOI: 10.1590/s0036-46652006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Cystoscopy in the diagnosis and follow-up of urinary schistosomiasis in Brazilian soldiers returning from Mozambique, Africa

Abstract: SUMMARYThe assessment of urinary schistosomiasis in individuals coming from endemic areas often requires diagnostic resources not used in areas of exposure in order to determine complications or to establish more precise criteria of cure. Cystoscopy and 24-hour urine examination were performed, after treatments with praziquantel 40 mg/kg body weight, single dose, on 25 Brazilian military men who were part of a United Nations peace mission to Mozambique in 1994. The median age of the individuals was 29 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…By the modifications of the Niamey protocol as proposed above, the assessment of the regression and subsequent reappearance of lesions in constantly exposed individuals might be evaluated more properly. A cystoscopy study on Brazilian soldiers returning from a peace keeping mission in Mozambique revealed that even after two rounds of adequate praziquantel therapy, 36% of soldiers who were no more excreting ova in the urine still had viable ova in the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 bladder mucosa (Silva et al 2006), an important issue also for travel medicine, considering the potential of schistosomiasis to induce bladder cancer (Mostafa, et al 1999, Amonkar et al 2001). Unfortunately; this study missed the opportunity to evaluate ultrasonography in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…By the modifications of the Niamey protocol as proposed above, the assessment of the regression and subsequent reappearance of lesions in constantly exposed individuals might be evaluated more properly. A cystoscopy study on Brazilian soldiers returning from a peace keeping mission in Mozambique revealed that even after two rounds of adequate praziquantel therapy, 36% of soldiers who were no more excreting ova in the urine still had viable ova in the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 bladder mucosa (Silva et al 2006), an important issue also for travel medicine, considering the potential of schistosomiasis to induce bladder cancer (Mostafa, et al 1999, Amonkar et al 2001). Unfortunately; this study missed the opportunity to evaluate ultrasonography in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…On returning from the mission, all participants presented S.haematobium eggs in the parasitological examination of urine and also urinary complications were attributed to the parasite. However, the transmission of this helminth did not occur in the American continent due to the inexistence of the host mollusk intercalated in the trematode life cycle (Silva et al, 2006). Ping et al (2014) and Wang et al (2013) cited that only S. japonicum is endemic.…”
Section: Discussionmentioning
confidence: 99%
“…1 Imported cases of schistosomiasis have been reported among tourist travelers, 2 immigrants, 3 expatriates, 4 Peace Corps volunteers, 5 and military personnel 6 with exposures to endemic areas of Africa or Asia.…”
mentioning
confidence: 99%